Israel's Knesset members : a comparative study of an undefined job - Rolef, Susan Hattis (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Taking Members of the Israeli Knesset as a case study, this book offers a comparative analysis of the role of Members of Parliament in democracies around the world"--
Keywords: Israel. -- Keneset; Israel. -- Keneset -- Case studies; Legislators -- Israel; Legislators -- Cross-cultural studies; Israel -- Politics and government; POLITICAL SCIENCE / Political Ideologies / Democracy; POLITICAL SCIENCE / Government / Legislative Branch